Keragaan Industri Rumah Tangga Aneka Kerupuk Hasil Laut di Kecamatan Socah-Kabupaten Bangkalan - Sugiarti, Teti (Universitas Trunojoyo Madura, 2009)
The study aimed to observe the various ojhousehold Industry in Sub Sea Cucumber Crackers Socah. This research method survey wzth interview techniques. Respondents numbered 23 processor chips. Primary data and secondary data. Research conducted, it can be concluded that 1) Profile of the entrepreneur is characterized byproductive age, low education but has a business experience a relatively long time. 2) Profile oJ the industry indicates that although the technology and production process zs relatively simple but highly pro pective business is viewed from the s pport and ease of raw ma!erial market. 3) Processing_ and Blonyo eggplant crackers are financzally profitable and provzde added value to the famzly of fi.shermen. and 4) Most busznesses rely on processor chips as the main incomefamilies. The contribution of these businesses contributed 50-90 percent offamily income. Processing should increase the proauction qzpacity, quality and product quality zn tenns ofl!ackaging and1icensing. 2) Keep the support offinanczal znstitutions or the government in an ejjort to strengthen business development and capital. and3) should be reactivated with business groups for perpetrators of agro-industries.Keywords: Domestic Industry, marine Results